The Influence of Social Media and Service Quality on the Decision to Use Diamond Event Organizer Services - Doloksaribu, Natalie Agatha P.; Sari, Dewi Comala (Journal of Economics and Social Sciences (JESS), 2025)
The rapid development of the business world requires business actors to continue to adapt, including in the event organizer (EO) service industry. Berlian Event Organizer is one company that has successfully utilized social media and provided quality services to attract consumer interest. This study aims to analyze the influence of social media and service quality on the decision to use services of Berlian Event Organizer. The method used is a quantitative approach with multiple linear regression analysis techniques. Research data was obtained by distributing questionnaires to 72 respondents who have used Berlian Event Organizer services. The results showed that the variables of social media (X1) and service quality (X2) have a positive and significant effect on the decision to use Berlian Event Organizer services, with the average respondent giving an affirmative answer. Based on the results of the T test, the social media variable (X1) has a significance value of 0.034 (<0.05) which means it has a significant effect on the decision to use services. Likewise, the service quality variable (X2) has a significance value of 0.000 (<0.05) which indicates a significant effect. The results of the simultaneous F test produced a significance value of 0.000, which means that social media and service quality together have a significant effect on the decision to use services. The coefficient of determination (R²) value of 0.845 indicates that 84.5% of the variation in service usage decisions can be explained by these two variables, while the remainder is influenced by other factors outside this study.